The Effect of Hypoplank Exercises on Muscular Endurance in Men Aged 35-40 Years Old - Mahmood, Dina; Abdulnebi, Hameed (Journal of Physical Education, 2022)
The importance of the research lies in mixing planks with hypoxic style in physical activity participants. The research aimed at designing exercises using hypoplank for men participants in physical activity aged 35 – 40. The researchers used experimental method on 130 men participating in fitness centers. A set of physical tests were applied including arms strength stamina, abdominal strength stamina tests, and 1000m running. The data was collected and treated to conclude that there are significant differences in favor of the experimental group in strength variables of arms, abdomen and 1000m running.